Donysia avia (Primulaceae), a new species from Zagros Mountains, Iran - Mehregan, Iraj; Younesi, Simin; Lidén, Magnus (Phytotaxa, 2021)
Dionysia avia, a new species from Esfahan province of Iran, is described, illustrated and compared with similar and related species. The new species is similar to D. bachtiarica and D. lamingtonii, but differs from the former mainly in showing isophylly and having abaxially pubescent leaves, pubescent calyx lobes and corollas, and capsules with 5–6 seeds, and can be distinguished from the latter mainly by its looser habit, softer and larger leaves, and calyx split to the base. A distribution map and a key to D. avia and similar species is provided.